The Catalogue of Palm Leaf Manuscripts kept in the Otani University Library. - Norman, K. R. (Buddhist Studies Review, 1997)
The Catalogue of Palm Leaf Manuscripts kept in the Otani University Library. Otani University Library, Kyoto 1995. lxxxi, 778 pp. No price given.